Pengaruh Insentif dan Disiplin Kerja terhadap Kinerja Pegawai pada Kecamatan Citangkil Kota Cilegon - Achmad Rozi (Entrepreneurship Faculty, Universitas Garut, 2019)
The present study is aimed at examining the influence of incentives and work disciplines on employee performance both partially and simultaneously in Cilegon, Indonesia. 31 of 102 Citangkil district officials were selected as sample respondents using Slovin’s formula. Based on the measurement scale on each item questionnaire, that the respondents were very disciplined and had good performance. The results of hypothesis testing show that incentives and work disciplines had influene on employee performance both partially and simultaneously. It can be concluded that the better the incentives, the better employee performance and that more disciplined the employees, the better their performance.